The Consistency of National Health Insurance Implementation in Achieving Health Equity - Asya, Jasran; Suryono, Arief; Makbul, Ahmad (Jurnal Hukum dan Kenotariatan, 2024)
The Constitution of the Republic of Indonesia mandates the state to fulfill health equity. The amendments to the Constitution reformed the health sector by decentralizing authority from the central government to regional governments. Both the regional and central governments share responsibility for health funding through public health efforts and individual health efforts. However, the National Social Security System Law and the Social Security Agency Law, which form the basis of the National Health Insurance program, were drafted and implemented without involving regional governments. This has widened the disparity in the availability of healthcare facilities and medical personnel between developed and underdeveloped regions. This research aims to assess the National Social Security System Law and the Social Security Agency Law in terms of their consistency with the Constitution and their synchronization with the Regional Government Law and the Health Law in achieving health equity. Additionally, it examines the role of regional governments in funding individual health efforts under the National Health Insurance program. This normative explanatory research, based on secondary data, investigates various legal norms related to the funding of individual health efforts by regional governments. The research concludes that the funding of individual health efforts under the National Health Insurance program by he Social Security Agency Law is inconsistent with the Constitution and is not synchronized with the Regional Government Law and the Health Law. Legislative corrections to the National Health Insurance program-related laws are necessary to involve regional governments.